The Coronavirus Crisis, Sustainable Development and the Incentive State Model - Báger, Gusztáv; Parragh, Bianka (Public Finance Quarterly, 2020)
To combat the coronavirus crisis and to deal with the challenges of sustainable development state should be more active and more efficient than before. This study presents the “philosophy”, directions, and first results of research aiming to define the new role of the state. By examining the effects of the positive and negative synergies of financial and ethical incentives on market participants, we may contribute to define new objectives and to implement them efficiently. Based on this approach and the related impact analysis, it can be stated that Hungary’s crisis management proved to be the most effective in June 2020 and the third most effective in October in the European Union. Another avenue of our research is to implement a complex, fourdimensional model supplemented by financial sustainability for analysing development, with a special focus on environmental sustainability and competitiveness. In this model, especially in its dynamic version, economic development is determined by the global megatrends and the Hungarian policies supporting the fulfilment of UN Sustainable Development Goals.